ANALISIS POLA SELEKSI, GRADASI, PRESENTASI DAN REPETISI KITÂB QOWÂ’ID AL-LUGHOH AL-‘ARABIYYAH KARYA MUHAMMAD YUSRON TAHUN 2022 - Asiyah, Dewi; Akhas, Muhammad Zayinil (Universitas Muhammadiyah Mataram, 2024)
This research is based on the existence of a theory of material analysis offered by William Francis Mackey, which the author examined by looking at the teaching materials of the book